Performance characterization of a novel marsh shoreline protection technology: The Wave Suppression and Sediment Collection (WSSC) system. (15th April 2018) - Besse, Grant; Sakib, Salman; Gang, Daniel; Hayes, Donald
Abstract: Minimizing coastal wetland loss is a high priority in coastal areas worldwide. Typical shoreline protection consists of hard structures placed near areas affected by wave action. These commonly used protection methods are costly, and may have negative impacts on the surrounding areas. The Wave Suppression and Sediment Collection (WSSC) system, made of multiple Wave Robber ® units, is an alternative shoreline protection structure. The primary goal of this study is to determine the performance characteristics of the technology in terms of energy coefficients. Experiments were performed on three scaled units within a laboratory wave tank. Performance characterization showed that the units have wave energy reflections of 0.47–0.83, transmission ranging from 0.10 to 0.42, and wave energy dissipation between 0.49 and 0.88, depending upon unit geometry and wave conditions. Performance data were also compared to other studies on shoreline protection structures. WSSC units reflect more wave energy and transmit less energy compared to other breakwater systems. These units could be utilized in coastal marshes with a large fetch, to reduce wave-induced erosion. Highlights: Wave reflection, transmission and dissipation coefficients were explored. WSSC units were good at attenuating long period waves. Efficiency comparison showed WSSC units reflect more wave energy compared to other breakwater systems. Type of coastal environment suitable for this technology was identified.